Cell wall synthesis and remodelling dynamics determine division site architecture and cell shape in Escherichia coli - Navarro, Paula P; Vettiger, Andrea; Ananda, Virly Y; Llopis, Paula Montero; Allolio, Christoph; Bernhardt, Thomas G; Chao, Luke H (Nature microbiology, 2022)
The bacterial division apparatus catalyses the synthesis and remodelling of septal peptidoglycan (sPG) to build the cell wall layer that fortifies the daughter cell poles. Understanding of this essential process has been limited by the lack of native three-dimensional views of developing septa. Here, we apply state-of-the-art cryogenic electron tomography (cryo-ET) and fluorescence microscopy to visualize the division site architecture and sPG biogenesis dynamics of the Gram-negative bacterium Escherichia coli. We identify a wedge-like sPG structure that fortifies the ingrowing septum. Experiments with strains defective in sPG biogenesis revealed that the septal architecture and mode of division can be modified to more closely resemble that of other Gram-negative (Caulobacter crescentus) or Gram-positive (Staphylococcus aureus) bacteria, suggesting that a conserved mechanism underlies the formation of different septal morphologies. Finally, analysis of mutants impaired in amidase activation (ΔenvC ΔnlpD) showed that cell wall remodelling affects the placement and stability of the cytokinetic ring. Taken together, our results support a model in which competition between the cell elongation and division machineries determines the shape of cell constrictions and the poles they form. They also highlight how the activity of the division system can be modulated to help generate the diverse array of shapes observed in the bacterial domain.
Keywords: buněčné dělení; Cell Division; tvar buňky; buněčná stěna; Amidohydrolases; Cell Wall; amidohydrolasy; Peptidoglycan; peptidoglykan; Cell Shape; Escherichia coli